طبقاتِ فقہائے حنفیہ؛ ابن کمال پاشا کا مؤقف اور بعض احناف کا ر د:تحقیقی مطالعہ: Ibn e Kamal Perspective on Tabqaat e fuqha Hanfia An Analytical Study - ڈاکٹر محمد ظفر اقبال جلالی; ماجد نواز ملک (Al Basirah, 2021)
The first of the Ahnafs, Ibn e Kamal Pasha divided the Fuqha e Hanafi'ah into seven classes, three of them belonging to Mujtahidin and four classes belong to the Muqaledin jurisprudents. The distribution was widely replicated in his books and Allama Tamimi termed this division as very good. This discussion of the jurisprudence of the jurists revealed the benefits of the jurisprudence of the jurists. Allama Marjani was the first to cash in on this division of Ibn Kamal Pasha. Allama Abdul Hai Lucknow was also not satisfied with this division and this division was also visible to him. When Allam Abd ul Hai Lakhnawi objected to class division, he quoted the objections in his book. Allama Qarshi also quoted Allama Marjani in his book "Hussan -ul -Taqqazi", and Allama Muta'i has raised objections to this class split in "Irshad Ahl-ul-Milla" and Abu Zahra in "Abu Hanifa Wa Hayatohoo". There is also cash on class division and objections to the jurisprudence mentioned under the classes. The reasons why the scholars who have cash in on this class division are those who say that An-i-Kamal did not explain the difference between the classes of jurists, nor did they have full knowledge of jurisprudence, since the jurists Most attributes are in common, so raising the position of a jurist and reducing the position of another jurist is a difficult task. And when Ibn Kamal studied the Books of Fatwa, some of the jurists found much of the Qur'anic verse, while other scholars who were simple and did not have much Qibla in their names, then Ibn Kamal was impressed with the alqabaat. And low-ranking jurists to lower. Keywords: Ibn e Kamal, Tabqat e Fuqha, , Marjani. Abd ul hayi.Abu Zahra .